An Industrialist - P. S. Deodhar - ., . (Journal of Engineering Education Transformations, 1997)
After getting his degree in Engineering with high honours in 1956, Mr . P. S. Deodhar spent several years in research and development before starting APLAB, the well respected manufacturer and exporter of Electronic instruments and systems.